PENGARUH KINERJA KARYAWAN DAN INDEPENDENSI TERHADAP KUALITAS AUDIT - Y, Andri Agustian (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2018)
This study was conducted to examine the influence of auditor employee performance and independence on the quality of internal audit. The purpose of the study is to know that with the employee performance and independence can improve the quality of internal audit. This research was conducted at PT. Pos Indonesia. Population in this research is auditor, finance and accounting department who work in PT. Pos Indonesia. The sampling technique was done by Simple Random Sampling with direct quizisoner spreading and obtained sample number 35 respondents. The primary data retrieval method used is the questionnaire method. Analysis method used to test the hypothesis is multiple linear regression. The statistical method used to test the classical assumption first, to test the hypothesis then used is t test and processed by using the program SPSS 24 For Windows. The results showed the influence of independence on the quality of internal audit of 13% this happens because it is easy to detect errors so as to facilitate the auditor in conducting the examination and easy to find the cause of the emergence of the error so easy to provide recommendations or findings to the company. The influence of performance on internal audit quality is 42% because the auditor is able to maintain objectivity and independence in conducting examination.